1990
DOI: 10.1002/bip.360290805
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hydration on the dynamic mechanical properties of elastin

Abstract: The dynamic mechanical properties of elastin have been quantified over a temperature and hydration range appropriate for a biological polymer. Composite curves of the tensile properties at constant water contents between 28.1 and 44.6% (g water/100 g protein) were typical of an amorphous polymer going through its glass transition. Water content had no effect on the shape of the curves, but shifted them a distance aC along the frequency axis. The combined effects of hydration and temperature are given in a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 35 publications
5
56
1
1
Order By: Relevance
“…The plots are master curves that were constructed by combining the results of dynamic tests taken at a number of temperatures, using the timetemperature superposition principle for polymeric materials. This process allows one to predict the behaviour of elastin at a reference temperature, in this case 37°C, over a much broader range of frequencies than can be achieved in laboratory tests (Gosline & French 1979;Gosline 1980;Lillie & Gosline 1990). The logic is that decreasing temperature slows molecular motion, so that mechanical tests carried out at a temperature below the reference temperature will reveal the behaviour at frequencies above the test frequency, and vice versa.…”
Section: The Functional Design Of Rubber-like Proteinsmentioning
confidence: 99%
“…The plots are master curves that were constructed by combining the results of dynamic tests taken at a number of temperatures, using the timetemperature superposition principle for polymeric materials. This process allows one to predict the behaviour of elastin at a reference temperature, in this case 37°C, over a much broader range of frequencies than can be achieved in laboratory tests (Gosline & French 1979;Gosline 1980;Lillie & Gosline 1990). The logic is that decreasing temperature slows molecular motion, so that mechanical tests carried out at a temperature below the reference temperature will reveal the behaviour at frequencies above the test frequency, and vice versa.…”
Section: The Functional Design Of Rubber-like Proteinsmentioning
confidence: 99%
“…Recently, water solvent was shown to act as a plasticizer for elastin (47), that is to say it enhances its mobility. Moreover, the action of solutes on the structure of elastin is indirect and seems to be mediated through its hydration shell (48).…”
Section: Fig 2 Nir Ft-r Spectrum Of Be In Powder In the Frequency Rmentioning
confidence: 99%
“…7 Several thermodynamic studies of elastin have indicated a strong dependence of the Young's modulus with the type of solvent and extent of hydration reinforcing the vital role of an aqueous environment that imparts its elasticity. [8][9][10] The strain dependence of the entropy and energy components of the stress for elastin samples in swelling equilibrium with different diluents has also been investigated. 11 It was shown that in water, the energetic component contributed $15% of the total stress.…”
mentioning
confidence: 99%